2021
DOI: 10.3390/w13172338
|View full text |Cite
|
Sign up to set email alerts
|

Application of Internal Carbon Source from Sewage Sludge: A Vital Measure to Improve Nitrogen Removal Efficiency of Low C/N Wastewater

Abstract: Biological nitrogen removal from wastewater is widely used all over the world on account of high efficiency and relatively low cost. However, nitrogen removal efficiency is not optimized when the organic matter has inadequate effect for the lack of a sufficient carbon source in influent. Although addition of an external carbon source (e.g., methanol and acetic acid) could solve the insufficient carbon source problem, it raises the operating cost of wastewater treatment plants (WWTPs). On the other hand, large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…The nitrification process occurs in two stages in the presence of oxygen, with ammonia (NH 4 + ) being oxidized to nitrite (NO 2 − ) by ammonia oxidizing bacteria (AOB) under aerobic conditions and then to nitrate (NO 3 − ) by nitrite oxidizing bacteria (NOB). Denitrification, on the other hand, is a process mediated by denitrifying bacteria (DNB) that converts nitrate or nitrite into nitrogen gas (N 2 ) in the absence of oxygen through intermediates of nitric oxide (NO) and nitrous oxide (N 2 O) (Wang et al, 2021). Furthermore, ethanol was used as an electron donor for oxidizing nitrate‐nitrogen to nitrogen gas during the heterotrophic denitrification process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nitrification process occurs in two stages in the presence of oxygen, with ammonia (NH 4 + ) being oxidized to nitrite (NO 2 − ) by ammonia oxidizing bacteria (AOB) under aerobic conditions and then to nitrate (NO 3 − ) by nitrite oxidizing bacteria (NOB). Denitrification, on the other hand, is a process mediated by denitrifying bacteria (DNB) that converts nitrate or nitrite into nitrogen gas (N 2 ) in the absence of oxygen through intermediates of nitric oxide (NO) and nitrous oxide (N 2 O) (Wang et al, 2021). Furthermore, ethanol was used as an electron donor for oxidizing nitrate‐nitrogen to nitrogen gas during the heterotrophic denitrification process.…”
Section: Methodsmentioning
confidence: 99%
“…) by nitrite oxidizing bacteria (NOB). Denitrification, on the other hand, is a process mediated by denitrifying bacteria (DNB) that converts nitrate or nitrite into nitrogen gas (N 2 ) in the absence of oxygen through intermediates of nitric oxide (NO) and nitrous oxide (N 2 O) (Wang et al, 2021). Furthermore, ethanol was used as an electron donor for oxidizing nitrate-nitrogen to nitrogen gas during the heterotrophic denitrification process.…”
mentioning
confidence: 99%
“…The complex nature of the CWW solution determines its inherent resourcing ability of material and energy transformation and makes possible a low-energy process for TN removal by managing the carbon source distribution in raw wastewater and optimizing multi-mode denitrification pathways. Pan et al and Ramos et al found that reduced compounds (e.g., SCN – , S 2– , CN – ) and easily degradable organic compounds (e.g., phenols and alkanes) in wastewater can be used as electron donors for denitrification to remove NO 3 – -N and NO 2 – -N. Wang et al investigated the feasibility of resource utilization of internal carbon sources within different wastewater treatment plants and found that primary hydrolysis reactor effluent and treated waste-activated sludge were suitable to be used as denitrification carbon sources and that organic matter after hydrolysis was among the most suitable internal carbon sources for biodegradation. The raw wastewater COD of CWW is about 3880 ± 250 mg L –1 , and the B/C ratio is around 0.5 ± 0.1.…”
Section: Introductionmentioning
confidence: 99%
“…Denitrifying bacteria require an organic carbon source as an electron donor and nitrate as an electron acceptor to reduce nitrate into pollution-free N 2 . However, the lack of a carbon source is a common problem faced by WWTPs, especially in southern China (Wu et al 2011; Wang et al 2021).…”
Section: Introductionmentioning
confidence: 99%